Experimental validation that human microbiome phages use alternative genetic coding - Samantha L. Peters; Adair L. Borges; Richard J. Giannone; Michael J. Morowitz; Jillian F. Banfield; Robert L. Hettich (Nature Communications, 2022)
Previous bioinformatic analyses have indicated that bacteriophages can use genetic codes different from those of their host bacteria. Here, Peters et al. use metaproteomics to provide experimental evidence of reassignment of stop codon TAG to glutamine in phages found in the human gut microbiome.